The role of perceived benefits in formation of intention to use Islamic crowdfunding platform among small and medium enterprises in Malaysia - Md Husin, Maizaitulaidawati; Haron, Razali; Aziz, Shahab (International Journal of Entrepreneurship and Management Practices (IJEMP), 2019)
Crowdfunding has become global phenomenon due to its possible role in providing equity funding to small and medium enterprises. Numerous benefits of crowdfunding have been identified. This paper investigated whether three factors - economic benefit, convenience and transaction process are important in influencing the perceived benefits of Islamic crowdfunding platforms, and whether perceived benefits affect small and medium enterprises’ (SMEs) intention to use the platform. Self-administered questionnaires and structured online surveys were distributed to SMEs in Selangor, Malaysia using the purposive sampling technique. SmartPLS was used to analyse the data. This paper found that economic benefit has a positive and significant relationship with perceived benefits, and transaction process has a negative and significant relationship with perceived benefits, while convenience was found to have an insignificant relationship with perceived benefits. This paper also found that perceived benefits was found to have a significant relationship with intention. The significance and contribution of this paper were also discussed.